2016
DOI: 10.1016/j.aim.2015.09.036
|View full text |Cite
|
Sign up to set email alerts
|

On quasisymmetry of quasiconformal mappings

Abstract: Suppose that f : D → D ′ is a quasiconformal mapping, where D and D ′ are domains in R n , and that D is a broad domain. Then for every arcwise connected subset A in D, the weak quasisymmetry of the restriction f | A : A → f (A) implies its quasisymmetry, and as a consequence, we see that the answer to one of the open problems raised by Heinonen from 1989 is affirmative under the additional condition that A is arcwise connected. As an application, we establish nine equivalent conditions for a bounded domain, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The introduction of quasimöbius maps has provided a handy tool when studying the quasisymmetric maps and the quasiconformal maps. Many references related to the relationships among quasimöbius maps, quasisymmetric maps and quasiconformal maps have been in literature; see [1,5,6,7,13,15,16,17,18,19,20,21,25,29,30] etc. The precise definition for quasimöbius maps is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of quasimöbius maps has provided a handy tool when studying the quasisymmetric maps and the quasiconformal maps. Many references related to the relationships among quasimöbius maps, quasisymmetric maps and quasiconformal maps have been in literature; see [1,5,6,7,13,15,16,17,18,19,20,21,25,29,30] etc. The precise definition for quasimöbius maps is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of this approach is that it avoids using volume integrals and conformal modulus, allowing one to study the quasiconformality of mappings in infinite dimensional Banach spaces and metric spaces without doubling volume measure. This line of research has recently attracted substantial interest, and some recent results can be found from [4,5,8,10] and references therein.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…This class of domains has numerous geometric and function theoretic properties that are useful in many fields of mathematical analysis (see e.g. [2,5,13,16,18]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Also, Väisälä proved the quantitative equivalence between free quasiconformality and quasisymmetry of homeomorphisms between two Banach spaces, see [48,Theorem 7.15]. Against this background, it is not surprising that the study of quasisymmetry in metric spaces has recently attracted significant attention [4,24,23,39,52].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%